Austria's separate gender roles model was popular in the past, but is becoming a constraint for comprehensive wellbeing - Gönenç, Rauf (OECD Economics Department Working Papers, 2015)
Austria has a model of "separate gender roles" in work, family and life arrangements which persists despite efforts to better balance these roles. Irrespective of their education level - which is higher for new generations than men's - the majority of women with children withdraw fully or partly from the labour force until their children reach school age, and beyond. This pattern has provided the Austrian population with generally high quality family services, but buttressed gender inequalities, and deprived society from the activation of existing talent, and therefore from additional household incomes, fiscal revenues and potential output. Gender differences in life-time career and income paths, well-being, and participation patterns in public life generate increasing dissatisfaction in growing segments of society, among both women and men